The effect of giving palm sugar on the physical condition of football school students - Abil Choiri; Jhony Hendra; Raja Bani Pilitan; Desi Tri Susanti; Ikhsan Maulana Putra (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problem: The low achievement of students at the Football School (SSB) is thought to be due to unstable physical conditions, lack of energy sources consumed by players, lack of nutritional intake by players, and players still consuming a lot of cold drinks before and after training. Objective: This study aims to determine the effect of giving palm sugar on the physical condition of students at the Football School (SSB). Method: The type of research is an experiment with a one group pre-test and post-test research design. The population in this study was 204 people. The sample was 24 people with a sampling technique using purposive sampling technique. The instruments in this study were endurance tests with a 1000 meter running test, speed tests with a 30 meter running test, strength tests with a wall squat test, agility tests with an illionis test. The data analysis technique in this study used the t-test. Results: The results of statistical analysis showed a significant difference between the average initial test and the final endurance test (t count = 8.980), the average initial test and the final speed test (t count = 6.965), the average initial test and the final strength test (t count = 8.112), the average initial test and the final agility test (t count = 9.070) with a t table value = 2.178. With a significance value (p-value) smaller than α = 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, that there is a significant difference between the average initial test and the average final physical condition test. Conversion of the physical condition component value, it is known that the initial test result of 3.6 is in the very poor category , and the final test result of 6.4 is in the sufficient category. These results indicate that there is a significant increase after giving palm sugar to the physical condition. Conclusion: Based on the research results, it can be concluded that there is an effect of giving palm sugar on the physical condition of students at the Football School (SSB).